2013
DOI: 10.1186/1477-7525-11-91
|View full text |Cite
|
Sign up to set email alerts
|

Scalability and internal consistency of the German version of the dementia-specific quality of life instrument QUALIDEM in nursing homes – a secondary data analysis

Abstract: BackgroundQuality of life (Qol) is a widely selected outcome in intervention studies. The QUALIDEM is a dementia-specific Qol-instrument from The Netherlands. The aim of this study is to evaluate the scalability and internal consistency of the German version of the QUALIDEM.MethodsThis secondary data analysis is based on a total sample of 634 residents with dementia from 43 nursing homes. The QUALIDEM consists of nine subscales that were applied to a subsample of 378 people with mild to severe dementia and six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
27
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 46 publications
7
27
0
1
Order By: Relevance
“…Although studies show reliable results of the QUALIDEM in nursing homes even for a short observation period of about 1 week,63 there are no studies that evaluate the reliability and validity for use in hospitals. We have done checks of internal consistencies, which showed that most subdomains of the QUALIDEM perform well with our data and are comparable with results from other validation studies 64. This indicates that the use of the QUALIDEM is feasible for hospital research.…”
Section: Discussionsupporting
confidence: 86%
“…Although studies show reliable results of the QUALIDEM in nursing homes even for a short observation period of about 1 week,63 there are no studies that evaluate the reliability and validity for use in hospitals. We have done checks of internal consistencies, which showed that most subdomains of the QUALIDEM perform well with our data and are comparable with results from other validation studies 64. This indicates that the use of the QUALIDEM is feasible for hospital research.…”
Section: Discussionsupporting
confidence: 86%
“…Next to the subscales, we created a composite sum score across all 37 items, which has been used extensively in the literature as well [25][26][27][28][29][30]. Thus, in our analyses, we look into both the comprehensive sum score (Table 2) as well as subscale results ( 'positive affect', 'negative affect', 'restlessness', and 'social relationships' of the full 37-item version of QUALIDEM (i.e., subscale B, subscale C, subscale D, and subscale F) [8,31]. As part of a workshop, the study team was selecting the items based on the following considerations: Two items from four subscales of the German QUALIDEM version were used for the short version.…”
Section: Methodsmentioning
confidence: 99%
“…Focusing on the psychosocial domains of QoL in PwD, the QoL assessment tool QUALI-DEM showed the best acceptability interviewing PwD and their proxies. It was considered as acceptable in the long and short forms profiling PwD with mild-to-very severe stages of dementia living in nursing homes [4,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Seine Praktikabilität wird als gut beurteilt (Bouman et al, 2011;Dichter, Bartholomeyczik, Nordheim, Achterberg & Halek, 2011;Gräske et al, 2014). Die Studien stützen die Validität des QUALIDEM, im Bereich Beziehung zu anderen Variablen besteht jedoch noch wenig Evidenz (Arons et al, 2018;Bouman et al, 2011;Dichter et al, 2011Dichter et al, , 2013Dichter et al, , 2014Dichter, Wolschon, Meyer & Kopke, 2016;Ettema, Dröes, de Lange, Mellenbergh & Ribbe, 2007b, 2007aGräske et al, 2014).…”
Section: Qualidemunclassified